Speaking with Authority: Reading Catherine of Siena in the Times of Vittoria Colonna - Stella, Clara (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
This article proposes a way of reading Vittoria Colonna’s lyric persona in the light of Catherine of Siena’s religious writings and philosophy of the self. In part 1, I begin by tracing the mystic profile that the participants of Colonna’s reformed circles ascribed to the saint. Those descriptions are then incorporated into a comparison of the schisms that shaped Christianity in Catherine’s times, namely the Avignon Papacy, and those of the Lutheran Reformation. In part 2, Colonna’s sacred charisma(s) is related to Catherine’s penitential and political model, thus identifying her Vita and epistles as a very possible literary source that Colonna could have used in her religious output and self-identification. In part 3, I analyze Colonna’s exegesis of the penitent Magdalene in the light of Catherine’s political reading of the same character. To conclude, I discuss the ways in which we can integrate the Trecento tradition into Colonna’s conception of grace and prophetic message of renovatio.